Six : all the songs from the hit musical - Marlow, Toby, 1994-; Moss, Lucy (Hal Leonard, 2020)
Six is a modern retelling of the lives of the six women who married Henry VIII. The women are forming an all-girl pop group and are competing for the title of lead singer.